HEALTH LITERACY AND ACCESSIBILITY TO HEALTH INFORMATION OF GROUP AT RISK OF HYPERTENSION: STUDY IN AKHA COMMUNITY AT MAE SUAI DISTRICT, CHIANGRAI PROVINCE - Gantagad, Tadsaneewan; Sareeso, Porntip; Prison, Piyaporn; Panya, Pattarika (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2020)
This qualitative research aims to examine health literacy and ability to the accessibility to health information among the Akha hill tribe. The study was carried out in the hill tribe village located in Mae Suai, Chiang Rai, Thailand. The data were collected by using a focus group with semi-structured interview related to health literacy and accessibility to health information, field note and audio-recording. The questionnaires used in the interview were examined the consistency of the questions and research objectives by 3 experts. Thirteen informants were selected based on the purposive selection technique. The informants were the persons who were at risk of hypertension. Data were recorded, transcribed word-for-word and analyzed using van Kamm’s method. The results revealed 3 domains. First, for that health behavior related to preventing hypertension scope, the informants had constantly had high fat meals and not done enough exercise. Second, for the health literacy related to hypertension and skills necessary to prevent hypertension aspect, it was found that the informants had the basic knowledge for preventing hypertension, but did not have the necessary skills to change their behavior to prevent hypertension. Moreover, communication about health to prevent hypotension was one-way communication. Third, on the topic of accessibility to health information related to preventing hypertension, it was found that informants did not know how to find information and lack adequate tools for searching. Therefore, health care providers should continue to promote access to online media related to health information for Akha people to increase their ability to retrieve health-related information.